CLINICAL STUDY ON MEROPENEM - Miki, Fumio; Tanizawa, Shinichi; Hiruma, Masahito; Ikuno, Yoshiyasu; Sakamoto, Kazuo; Murata, Akihito (CHEMOTHERAPY, 1992)
Meropenem (MEPM) was adiministered by intravenous drip infusion at 500 mg b.i.d. to four patients with respiratory tract infections for 3 to 14 days. The clinical responses were good in two and poor in one of the three cases of bacterial pneumonia and poor in one case of infected lung cancer. One strain each of Haemophilus influenzae and Streptococcus pneumoniae was eradicated by administration of MEPM. Apart from one case of transiently and slightly elevated GOT and GTP, no adverse reaction or abnormal laboratory findings were noted following adminstration of MEPM.